Rh and Kell phenotyping in voluntary blood donors: A study from a tertiary care blood center of western India - Sangita D. Shah; Nidhi M. Bhatnagar; Mamta C. Shah; Garima H. Thakkar; Ujjwal Ahuja; Anu Patel; Drashti Gajera; Priya G. Kalavadiya (Asian Journal of Transfusion Science)
INTRODUCTION: In human beings, there are 45 blood group systems and 360 antigens currently recognized by ISBT (July 2023). The Rh blood group system has 56 antigens, out of them 5 antigens D, C, c, E, and e are clinically significant antigens. The Kell blood group system has 25 highly immunogenic antigens. Cases have been reported where IgG-type of antibodies against Rh and Kell antigens are found which are responsible for transfusion reactions and hemolytic disease of newborn. AIMS AND OBJECTIVES: To study the prevalence of Rh-Kell phenotype in voluntary blood donors, To provide Rh and Kell antigen-matched blood products to patients to prevent alloimmunization, To make a donor directory of Rh and Kell phenotyped donors for further use. MATEIALS AND METHODS: The antigen typing for Rh antigens (D, C, c, E, and e) and Kell (K) was performed on the collected ethylenediaminetetraacetic acid samples from 1014 voluntary donors. The test was performed by Erythrocyte Magnetic Technique using a microplate (DuoLys) in a fully automated immunohematology system (Diagast Qwalys Evo 3 instrument). RESULTS: From 1014 phenotyped donors, the most common antigen frequency was of “e” (98.6%) followed by “D”(96.2%),“C”(89.4%), “c”(54.8%), and “E”(18.6%). The frequency of the “K” antigen was (1.38%). The most common Rh phenotype from the study population was R1R1(CDe/CDe) (45%) and the rarest was r’r’ (Ce/Ce) (0.1%). CONCLUSION: Knowledge of the phenotype frequency in the local population is helpful in making a donor directory, In situations where clinically significant alloantibodies are found in patient’s serum, antigen-negative blood unit can be arranged using a donor directory.